Sustaining Community-Based Responses to the COVID-19 Pandemic: Learning Platforms at Work in Freetown, Sierra Leone. (May 2022) - Koroma, Braima; Macarthy, Joseph Mustapha; Conteh, Abu; Osuteye, Emmanuel
In Freetown, Sierra Leone, despite the progress in the official response to the COVID-19 outbreak, there remain concerns about the limited involvement of local communities and the use of bottom-up participatory approaches in the response. While the official response has been characterised by restrictive public health measures such as partial lockdowns and the declaration of a state of a public health emergency, for the urban poor, the implications have been wide-ranging including the deepening of inequalities, especially among residents in slum-like informal settlements who already suffer from pre-COVID-19 structural challenges and vulnerabilities. This includes challenges linked to health systems fragility, environmental risks and uncertainties around livelihoods in the informal economy, which forces many to live from hand to mouth. Ultimately, these vulnerabilities challenge the acceptance and compliance of the restrictive state-led health measures, which puts them at risk of infections. To address these structural inequalities and foster an inclusive dialogue, a City Learning Platform, comprising the Freetown City Council, local community residents and their groups, and a few non-governmental organisations have been working creatively to respond to the COVID-19 challenges faced by the urban poor. But, while this alternative bottom-up approach has allowed the coordination of response to address community-level priorities more effectively, how well the platform has been able to successfully sustain the interest and commitments of vulnerable groups and to build their capacities, co-create knowledge and explore new opportunities has yet to be understood. This article highlights the strategic value of Community Learning Platforms in sustaining local responses to the pandemic. It also explores how social protection measures are shaped into the local response and help tackle deeply entrenched inequalities in the communities. The article additionally reflects on the challenges and opportunities for using the Community Learning Platforms in the COVID-19 response.